Sliding mode control for T–S fuzzy singular semi-Markovian jump system. (November 2018) - Zhang, Di; Zhang, Qingling
Abstract: This paper presents sliding mode control for nonlinear singular semi-Markovian jump system by Takagi–Sugeno(T–S) fuzzy technique. By intentionally introducing a proper delay, an integral sliding surface is defined. This method considers the information about the current and delayed state. The obtained sliding motion is a T–S fuzzy singular semi-Markovian jump time-delay system. It is shown that this kind of integral sliding mode control can improve the control performance when the artificial delay is added to the integral sliding mode surface. Finally, the application and the merits of the obtained results are introduced by two examples.